Operationalizing the Deployment of Low-Titer O-Positive Whole Blood Within a Regional Trauma System. (25th January 2021) - Schaefer, Randall; Long, Tasia; Wampler, David; Summers, Rena; Epley, Eric; Waltman, Elizabeth; Eastridge, Brian; Jenkins, Donald
ABSTRACT: Introduction: The implementation of a low-titer O+ whole blood (LTOWB) resuscitation algorithm, particularly in the prehospital environment, has several inherent challenges, including cost, limited and inconsistent supply, and the logistics of cold-chain management. The Southwest Texas Regional Advisory Council has implemented the nation's first multidisciplinary, multi-institutional regional LTOWB program. This research effort was to illustrate the successful deployment of LTOWB within a regional trauma system. Materials and Methods: A deliberate systems approach to the deployment of LTOWB was used. Tenets of this program included the active management of blood donor sources and blood supply levels to minimize wastage as a result of expiration, maximize product utilization, the use of prehospital transfusion triggers, and efforts to decrease program costs prehospital agencies. A novel LTOWB rotation system was established using the concept of a "rotation site" and "rotation center." Standardized transfusion criteria, a regional approved equipment list, a regional Prehospital Blood Product Transfusion Record, and a robust multilevel communication plan serves as the framework for the program. The San Antonio Whole Blood Consortium was developed to create a consensus driven forum to manage and guide the program. Results: From January 2018 to October 2019, LTOWB has been placed at 18 helicopter emergency medical services (HEMS) bases, 12 ground emergency medical service (EMS) agencies, 1 level I trauma center, and 1 level IV trauma center. A total of 450 patients have received a prehospital LTOWB transfusion. Program wide, the wastage rate of LTOWB due to expiration is between 1% and 2%. No complications related to prehospital LTOWB administration have been identified. Discussion: This work demonstrates a novel model for the development of a trauma system LTOWB program. The program's implementation augments remote damage control resuscitation strategies and requires the integration and collaboration of a multidisciplinary stakeholder team to optimize efficiency, performance, and safety of the program.